Understanding HIV care providers’ support for tobacco cessation among people living with HIV in Western Kenya: a formative qualitative study - Peter Magati; Maya Vijayaraghavan; Elizabeth A Bukusi; Craig R Cohen; Starley B Shade; Zachary Arochi Kwena; Linet Ongeri; Francesca A Odhiambo; Cirilus O Ogala; Yvonne A Olando; Greshon Rota; Purba Chatterjee; et al. (BMJ Public Health, 2024)
Introduction Healthcare providers are required to support people living with HIV (PLHIV) to quit tobacco use for improved health outcomes, but it is unclear to what extent they adhere to these requirements. We examined HIV care providers and PLHIV’s perceptions of support, and barriers, to providing tobacco cessation.Methods This qualitative investigation was part of a larger study seeking to integrate tobacco cessation into HIV care in Western Kenya (NCT05351606). We conducted 22 key informant interviews with HIV care providers and managers and four focus group discussions (n=28) with PLHIV. The interviews and discussions were audio-recorded, and audio files were transcribed and, when necessary, translated into English for coding and analysis.Results PLHIV rarely disclose or are screened for tobacco use unless a complaint or clinical finding prompts a provider. Despite PLHIV wanting to receive support to quit tobacco use, they feared negative reactions from their providers if they disclosed their tobacco use status. Providers cited several system-related barriers to screening for and providing cessation support for PLHIV, including workload pressure, lack of job aids, tobacco use screening not included as a performance indicator and lack of adequate counselling skills to address tobacco use.Conclusions PLHIV are not routinely screened for tobacco use despite their knowledge of the negative impact of tobacco use on overall health outcomes and desire to quit. System-related barriers hinder providers from providing cessation support. Providers should be trained and equipped with additional skills and resources to integrate tobacco cessation support into routine HIV care.